PENGARUH STRATEGI PEMASARAN TERHADAP LOYALITAS PELANGGAN BUTIK BUSANA MUSLIM ANISA KOTA GORONTALO - Mardiana, Andi; Kasim, Nur Ain (Li Falah: Journal of Islamic Economics and Business, 2016)
Abstact This study aims to assess the marketing strategy consisting of product quality and price factors on customer loyalty in the Boutique Clothing Annisa Gorontalo City, with a total sample of 100 respondents. This type of research used in this research is the kind of research with quantitative approach. The method used is the method of observation using a questionnaire. This study uses multiple regression analysis on primary data found that product quality factor positive effect on customer loyalty and positive berpengruh price to customer loyalty. The results of simultaneous hypothesis test (test F) of two independent variables with f count of 24.022 are located in the area reject H0. This means that at the same time a lot of quality products and price factor has a positive and significant impact on customer loyalty boutique Anisa Gorontalo. The coefficient of determination of two independent variables obtained yield was 0.561. This means that the ability of a lot of quality products and price factors in explaining the loyalty of 56.1% remaining 43.9% is influenced by other variables not included in this study